PENGARUH VARIABEL MIKROEKONOMI DAN MAKROEKONOMI TERHADAP FLUKTUASI HARGA SAHAM (STUDI KASUS PADA SAHAM IDX-30 SEKTOR PERBANKAN PERIODE 2020-2021) - Muhammad Pratama Yudha Kusuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The COVID-19 pandemic has an impact on all aspects of life, especially in the capital market, which is marked by fluctuations in the JCI movement and stock prices. . The purpose of this study was to determine the effect of microeconomic factors consisting of Stock Trading Volume variables, Earning Per Share and macroeconomic factors consisting of the Shanghai Stock Exchange and Exchange Rate variables on stock price fluctuations. The time period used in this study is from 2020-2021. The population used is members of 30 IDX-30 Index companies. The sampling technique used was the purposive sampling technique. The sample of this research uses 6 banking sub-sector companies that are members of the IDX-30 index. This study uses panel data regression analysis method with the help of software Eviews. The model chosen is the Fixed Effect Model (FEM). The results of this study indicate that the stock trading volume and exchange rate variables have no effect on stock prices, while the Earning Per Share and Shanghai Stock Exchange variables have a positive and significan effect on stock prices.